2009
DOI: 10.1093/jjco/hyp050
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Docetaxel with Cyclophosphamide as Adjuvant Chemotherapy for Japanese Breast Cancer Patients

Abstract: Objective: The 7-year follow-up of the US oncology 9735 trial demonstrated the superiority of TC [docetaxel (DTX)/cyclophosphamide (CPA)] to doxorubicin/CPA therapy. To introduce TC therapy in Japan, the verification of the safety and tolerability is essential. We performed a collaborative prospective safety study with Okayama University to introduce TC therapy. Methods: The subjects were 53 patients aged from 33 to 67 years at intermediate risk based on the St Gallen risk classification who underwent radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 17 publications
(15 reference statements)
3
33
0
Order By: Relevance
“…Neither prophylactic antibiotics nor GCSF were routinely used in this trial. The incidence of FN and the completion rate were 28.3% and 94.3% in TC four cycles in Japanese patients (Takabatake et al, 2009), and the incidence of FN and the completion rate in this study were 13.6% and 86.4%, respectively. There was no significant difference between these two reports.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Neither prophylactic antibiotics nor GCSF were routinely used in this trial. The incidence of FN and the completion rate were 28.3% and 94.3% in TC four cycles in Japanese patients (Takabatake et al, 2009), and the incidence of FN and the completion rate in this study were 13.6% and 86.4%, respectively. There was no significant difference between these two reports.…”
Section: Discussionsupporting
confidence: 47%
“…In Japan, four cycles of TC therapy has become more common and its compliance was found to be tolerable (Takabatake et al, 2009). The PACS01 trial reported that sequential adjuvant chemotherapy with three cycles of fluorouracil, epirubicin and cyclophosphamide (FEC) followed by three cycles of docetaxel significantly improved DFS and OS , and we reported previously that the T-FEC regimen might be more tolerable than FEC followed by docetaxel in Japanese breast cancer patients (Abe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of fn for several chemotherapy regimens has been widely described within the context of clinical trials, only a few studies have described the occurrence of fn in clinical practice [19][20][21][22][23] . Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…We assumed twice the fn risk with tc than with ac and comparable base case utilities for both regimes during the treatment period. However, in clinical practice, tc chemotherapy is perhaps more commonly used in older patients and in those with node-negative disease, and it is associated with higher fn rates and possibly with lower treatment-related utility 27,[31][32][33] . Our cost-utility estimates in those practical scenarios, and in circumstances in which primary g-csf prophylaxis is considered for all patients, were less favorable than those in the primary analysis based on clinical trial data, although they remained within commonly used cost-utility thresholds 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The base case scenario incorporated secondary prophylaxis with granulocyte colony-stimulating factor (g-csf) after fn events and assumed no chemotherapy dose adjustments. However, outside of clinical trials, use of tc appears to be associated with higher fn rates of approximately 26% (range: 10%-46%) without and 6% (range: 0%-7%) with primary g-csf prophylaxis 27,31,32,33 . Primary prophylaxis with g-csf is also sometimes used with the tc regimen in clinical practice, because it is recommended for chemotherapeutic regimens associated with a fn risk greater than 20% 34 .…”
Section: Model Assumptionsmentioning
confidence: 98%